Changes in Denitrifier Abundance, Denitrification Gene mRNA Levels, Nitrous Oxide Emissions, and Denitrification in Anoxic Soil Microcosms Amended with Glucose and Plant Residues - Henderson, Sherri L. (American Society for Microbiology (ASM), 2010)
In agricultural cropping systems, crop residues are sources of organic carbon (C), an important factor influencing denitrification. The effects of red clover, soybean, and barley plant residues and of glucose on denitrifier abundance, denitrification gene mRNA levels, nitrous oxide (N(2)O) emissions, and denitrification rates were quantified in anoxic soil microcosms for 72 h. nosZ gene abundances and mRNA levels significantly increased in response to all organic carbon treatments over time. In contrast, the abundance and mRNA levels of Pseudomonas mandelii and closely related species (nirS(P)) increased only in glucose-amended soil: the nirS(P) guild abundance increased 5-fold over the 72-h incubation period (P < 0.001), while the mRNA level significantly increased more than 15-fold at 12 h (P < 0.001) and then subsequently decreased. The nosZ gene abundance was greater in plant residue-amended soil than in glucose-amended soil. Although plant residue carbon-to-nitrogen (C:N) ratios varied from 15:1 to 30:1, nosZ gene and mRNA levels were not significantly different among plant residue treatments, with an average of 3.5 × 10(7) gene copies and 6.9 × 10(7) transcripts g(−1) dry soil. Cumulative N(2)O emissions and denitrification rates increased over 72 h in both glucose- and plant-tissue-C-treated soil. The nirS(P) and nosZ communities responded differently to glucose and plant residue amendments. However, the targeted denitrifier communities responded similarly to the different plant residues under the conditions tested despite changes in the quality of organic C and different C:N ratios.